Breaking down barriers; unravelling the root causes and effects of brain drain in Pakistan - Sarwar, Mahwish; Syeda Laiba Fahim; Naveen Murad Khatoon (Journal of the Pakistan Medical Association, 2024)
Respected Editor, The term ‘brain drain’ refers to the migration of highly skilled and educated professionals from one country to another in search of better employment and living conditions. Brain drain has a detrimental impact on developing nations, leaving a counterproductive outcome due to the depletion of skilled human resources. According to the Pakistan Overseas Employment Corporation, around 21,000 professionals have migrated to other countries in the last 15 years.1 Brain drain has a pervasive effect across various domains, with healthcare being primarily one of the greatly affected. The most prevalent reason is the insufficient stipends and substandard workplace settings for professionals. Doctors work tirelessly yet are forced to face the injustice of the system, incidents of violence, and exploitation at the hands of their superiors. Most doctors (83%) agreed that meager salary packages and inequitable overtime duties motivated them to move abroad.2 Political instability in Pakistan has also affected the resettlement of healthcare individuals nationwide. Up to 81% of doctors are compelled to leave the country due to constant political turmoil.3 Blatant misogyny and cultural bounds have deterred women from working, contradicting the high female enrollment in medical colleges of Pakistan. Moreover, because of the brain drain, Pakistan is losing an insurmountable intellectual capital and educational investment, resulting in enormous pressure on the healthcare professionals who stay behind, contributing to the collapse of the already vulnerable system. Usually, the emigrants are of the privileged class which creates disparity because the ones left behind end up facing impecunious conditions and unfair working hours. The migration rate of healthcare professionals in Pakistan is increasing progressively. The United States, the United Kingdom, Canada, and Australia are four high-income countries where 56% of international medical graduates (IMGs) emigrate from low-income countries to have a better quality of life, monetary incentives, job opportunities, better education, and training. Furthermore, just three nations India, Pakistan, and the Philippines are home to 45% of IMGs.4,5 Therefore, we suggest that the government adopt strategies that will accommodate doctors, introducing remunerative packages and more employment opportunities to persuade them to serve their nation. The government should ameliorate the workplace environment to international standards, ensuring the safety and security of the professionals. Additionally, educational and training grounds should be provided to individuals to develop their skills. These immediate measures must be taken to minimize the escalating brain drain and aid in revamping the healthcare system of Pakistan.